Ready For Ai? A Systematic Review of EFL Teacher Perceptions and Professional Development in Asia - Dedi Aco (Balla' Caradde Education, 2026)
The rapid adoption of Chat GPT and generative artificial intelligence (AI) since November 2022 has transformed English as a Foreign Language (EFL) instruction, yet evidence on teachers’ perspectives across Asia remains fragmented. Addressing this gap, this systematic literature review synthesized empirical research on EFL teachers’ perceptions and professional development needs using the PRISMA 2020 framework. Peer-reviewed studies published between November 2022 and February 2026 were retrieved from six databases, with 15 studies from six Asian countries meeting the inclusion criteria. The findings reveal that teachers are cautiously optimistic, recognizing ChatGPT’s potential to enhance lesson planning and instructional efficiency while expressing concerns about accuracy, academic integrity, student over-reliance, and insufficient training. Across all studies, urgent professional development needs emerged, particularly in AI literacy, pedagogical integration, prompt engineering, and ethical practice. This review provides the first cross-national synthesis of these issues, offering evidence-based directions for policy, teacher education, and future research.